Annual Report of the Chief Medical Officer 1984 (Ministry of Health KingstonJM, 1986)
Provides general information on geography and climate of Jamaica as well as its basic social and economic data. Discusses health situation by focusing on vital statistics, mortality, morbidity, and communicable diseases. Lists three categories of health services viz. services to individuals, environmental services, support services, and discusses their utilization. Examines the health infrastructure by outlining organization of health services, health policy and health information system. Reviews the health resources of the ministry viz. its manpower, its facilities, and its finance. Concludes with map showing health facilities in Jamaica.
IDS